2008
DOI: 10.1086/524342
|View full text |Cite
|
Sign up to set email alerts
|

Lyman Break Galaxies, Lyα Emitters, and a Radio Galaxy in a Protocluster atz= 4.1

Abstract: We present deep HSTACS observations in g 475 r 625 i 775 z 850 toward the z ¼ 4:1 radio galaxy TN J1338À1942 and its overdensity of >30 spectroscopically confirmed Ly emitters (LAEs). We select 66 g 475 band dropouts to z 850;5 ¼ 27, 6 of which are also LAEs. Although our color-color selection results in a relatively broad redshift range centered on z ¼ 4:1, the field of TN J1338À1942 is richer than the average field at the >5 significance, based on a comparison with GOODS. The angular distribution is filament… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
140
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 140 publications
(245 reference statements)
17
140
0
1
Order By: Relevance
“…We here checked the overlap of our sample with previous studies. We cross-matched the coordinates of our sources with LAEs in the sample of Venemans et al (2007) and LBGs in Overzier et al (2008), both observing the same field. We found E N Figure 3.…”
Section: The Tnj1338 Field Samplementioning
confidence: 99%
See 1 more Smart Citation
“…We here checked the overlap of our sample with previous studies. We cross-matched the coordinates of our sources with LAEs in the sample of Venemans et al (2007) and LBGs in Overzier et al (2008), both observing the same field. We found E N Figure 3.…”
Section: The Tnj1338 Field Samplementioning
confidence: 99%
“…It has been suggested that this source is associated with a highly overdense region traced by LAEs and Lyman-break galaxies (LBGs), and thus represents an ancestor of present-day clusters, i.e. a protocluster (Venemans et al 2002(Venemans et al , 2007Miley et al 2004;Intema et al 2006;Overzier et al 2008). Theoretical simulations also suggests that the overdensity associated with TNJ1338 is likely to be an ancestor of a present-day cluster (Chiang, Overzier & Gebhardt 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Narrow line emitter surveys of HzRGs at 2 < z < 5 show that they are often located in overdense regions, designated as 'protoclusters' that are likely to be the progenitors of the present day massive groups and clusters (Venemans et al 2002(Venemans et al , 2005(Venemans et al , 2007Pentericci et al 2000;Kurk et al 2004). The narrow line emitters are, however, only a low-mass subset of the general population of UV-selected, star forming galaxies Overzier et al 2008) and likely do not represent the majority of the total stellar mass.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative technique, which is employed especially for searches of the high-redshift universe, is to perform narrow-band imaging or photometric redshift searches around massive radioloud quasars or other types of powerful active galactic nuclei (AGN) (e.g., Kurk et al 2004;Miley et al 2004;Venemans et al 2004Venemans et al , 2005Zheng et al 2006;Overzier et al 2008;Kuiper et al 2010Kuiper et al , 2011Kuiper et al , 2012. Such phenomena are typically associated with massive galaxies, which are, in turn, typically associated with galaxy overdensities.…”
mentioning
confidence: 99%